1998
DOI: 10.1246/cl.1998.117
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric Decomposition of Pure Water over Pt-Loaded Ti/B Binary Oxide under UV-Irradiation

Abstract: A titanium-boron binary oxide has been prepared by the sol-gel method and used as a photocatalyst for the decomposition of water. The structure of titanium oxide species in the Ti/B binary oxide was amorphous before and crystal after calcination in O2, while the boron oxide species retained its amorphous state. Pt-loaded Ti/B photocatalysts were found to decompose water stoichiometrically in aqueous suspension systems. Their photocatalytic activities decreased markedly with increase in the calcination temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…On the NaOH-coated photocatalyst [10][11][12][13][14][26][27][28], the coated NaOH layers serve to keep enough water on the photocatalyst to sustain the efficient photocatalytic decomposition of water. Moon et al [35][36][37][38] have reported on titanium oxide modified with boron (B/TiO 2 ) and prepared by a sol-gel method which exhibited remarkable photocatalytic activity for the decomposition of water. It is well known that boron oxides can interact strongly with water molecules and easily becomes moist in air [39,40], a great advantage in the efficient decomposition of water, thus, improving the photocatalytic reactivity.…”
Section: New Methods For the Improvement Of Water Decompositionmentioning
confidence: 99%
“…On the NaOH-coated photocatalyst [10][11][12][13][14][26][27][28], the coated NaOH layers serve to keep enough water on the photocatalyst to sustain the efficient photocatalytic decomposition of water. Moon et al [35][36][37][38] have reported on titanium oxide modified with boron (B/TiO 2 ) and prepared by a sol-gel method which exhibited remarkable photocatalytic activity for the decomposition of water. It is well known that boron oxides can interact strongly with water molecules and easily becomes moist in air [39,40], a great advantage in the efficient decomposition of water, thus, improving the photocatalytic reactivity.…”
Section: New Methods For the Improvement Of Water Decompositionmentioning
confidence: 99%
“…The first report on water splitting via harvesting photon energy is authored by Fujishima and Honda using a photoelectrochemical cell with a TiO 2 photoelectrode [7]. Following this first report suggesting the oxidation of water molecule via photogenerated holes on TiO 2 surface with the aid of small electrical voltage, photocatalytic water splitting on powder photocatalyst particles is demonstrated by other authors in the late twentieth century [8][9][10][11][12][13][14][15]. Metal-loaded semiconductors (such as Pt/TiO 2 ) are described as "short-circuited photoelectrochemical cells" that provide both the oxidizing centers and the reduction centers on the same catalyst (see Figure 1) [16].…”
Section: Photocatalysis and Water Splittingmentioning
confidence: 96%
“…The development of an active catalyst for the photocatalytic decomposition of pure water into H 2 and O 2 is urgently required from an energy‐saving viewpoint. Various semiconductor oxides, mainly TiO 2 ‐ and Nb‐based mixed oxides, have been investigated for this reaction 1. 2 Recently, however, various Ta‐based oxides reported by Kato and Kudo et al have attracted interest as new photocatalytic materials because of their fairly high activity for the photocatalytic splitting of H 2 O 35.…”
Section: Photocatalytic Splitting Of Water Into H2 and O2 By K095ta0mentioning
confidence: 99%